Foreign Direct Investment, Non-Oil Exports, and Economic Growth in Nigeria: A Causality Analysis - Olayiwola, Kolawole; Okodua, Henry (Asian Economic and Financial Review, 2013)
The study examines the contribution of Foreign Direct Investment (FDI) to the performance of non-oil exports in Nigeria within the framework of the export-led growth (ELG) hypothesis. Available evidence in Nigeria supports that the bulk of FDI inflow into the country goes to the oil sector of the economy. From the perspective of efficiency-seeking FDI, foreign capital always aims at taking advantage of cost-efficient production condition. Given this fact, a causality analysis was undertaken in order to verify the relevance of the ELG hypothesis. Also, the dynamic interaction among FDI, non-oil exports, and economic growth is investigated using the concept of variance decomposition and impulse response analysis. The results obtained from the causality analysis revealed that a unidirectional causality runs from FDI to non-oil exports. Each of the three variables exhibited on the average and at the early stages of the out-of-sample forecast period, a dormant response to one standard deviation shock or innovation. However, they all demonstrated significant responses after some 7 years into the out-of-sample forecast period. The results also show that an encouragement of non-oil exports is a necessity for an effective FDI in Nigeria. Therefore, in designing policies towards this direction, policy response lag need to be taken into consideration.